"Integration Constellations" – The Interaction between Destination and Origin Countries and Civil Society Organizations in Migrant Integration. (11th February 2019) - Salamońska, Justyna; Unterreiner, Anne
Abstract: Mainstream migration research examines migrant integration mainly as a function of integration policies in the country of destination, paying relatively little attention to policy frameworks in the country of origin. In this article we introduce the concept of "integration constellations" in order to describe multiple actors and actions involved in migrant integration in Europe. The analysis of such constellations includes policies frameworks produced by countries of destination and by countries of origin along with activities by civil society organizations. Our study encompasses all these actors in examining three empirical cases: Chinese student migration to the UK, Iranian refugees in Sweden, and Ukrainian labour migrants in Poland. These examples illustrate how actions by the states of origin and of destination can either complement or oppose each other. Although we concentrate on just three dimensions of integration (education, labour market and political participation), we point out the multidimensional reality of migrant integration.